A Novel Mutation c.3392G>T of COL2A1 Causes Spondyloepiphyseal Dysplasia Congenital by Affecting Pre-mRNA Splicing - Fan, Lihong; Ji, Longfei; Xu, Yuqing; Shen, Guosong; Tang, Kefeng; Li, Zhi; Ye, Sisi; Shen, Xueping (Frontiers in Genetics, 2022)
Spondyloepiphyseal dysplasia congenital (SEDC) is a rare chondrodysplasia caused by dominant pathogenic variants in collagen type II alpha 1 (COL2A1). Here, we detected a novel variant c.3392G>T of COL2A1 in a Chinese family with SEDC by targeted next-generation sequencing. Then the minigene analysis was carried out based on HeLa and HEK293T cell lines. Splicing assay indicates that the mutated minigene produces an alternatively spliced transcript with a skipping of exon 48, which generated an in-frame deletion of 15 amino acids (p. Gly1131_Pro1145del) in the COL2A1 protein. Due to the pathogenicity of the variation, we performed prenatal diagnosis on the proband’s wife, which indicated that the fetus carried the same mutation.